Upaya Pemerintah Dalam Mengelola Diversity Sumber Daya Manusia Di Kecamatan Gunungsitoli Barat - Zebua, Evi Trisanti; Ndraha, Ayler Beniah; Lahagu, Palindungan; Hulu, Fatolosa (Journal of Accounting and Finance Management, 2024)
Kecamatan Gunungsitoli Barat is an area rich in cultural diversity, religion and strong customary traditions, and is inhabited by people with diverse ethnic backgrounds, including Batak and Malay. This diversity, although a great potential, also presents challenges for sub-district government organizations, especially in managing ethnic and cultural differences that can trigger social tensions. Issues of discrimination and unequal access to economic resources and employment opportunities are also issues that require serious attention. In addition, the limited political participation of some groups threatens the balance of representation in the sub-district government. This research uses a qualitative approach with a case study method to identify the challenges faced by the sub-district government in managing human resource diversity. The results show that appropriate strategies and policies are needed to create harmony in managing such diversity. Three main efforts that can be made by the sub-district government include: a) organizing cross-cultural training programs, b) implementing inclusive policies to ensure equal opportunities for all individuals, and c) building a monitoring and evaluation system to ensure effectiveness and transparency in managing HR diversity.